ENVIRONMENTAL POLLUTION AND HEALTH HAZARDS : AN AWARENESS STUDY IN THE REPRODUCTIVE AGE BRACKETS - Patro, Lingaraj (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
The purpose of the study is to understand the sensitivity of adult groups to environmental pollution. The project was carried out by collecting information from the respondents of reproductive age groups using structured interview schedules. The interview schedule was pretested by a pilot study and necessary modifications were done. The data were assigned with percentage scores for a quantitative analysis. The awareness level was evaluated from the stand points of air, water, soil, noise, radiation and thermal pollution. The responses were compiled and interpreted from the objective point of view. The results revealed that among the pollution categories most of the samples were mostly aware of air, water, soil and noise pollution and very few knew about thermal and radiation pollution. Table-1 depicts awareness level of samples with regard to environmental pollution. Information shows that a great number of samples (85 %) were aware of air and water pollution, 80 % of samples were aware of soil and noise pollution, 60% of samples were aware of thermal pollution and only 50 % samples were aware of radiation pollution. Table -2. Reveals that 25 % of the samples were aware of sources of soil pollution and noise pollution, similarly 20 % of the samples were aware of sources of air pollution, water pollution and thermal pollution and only 15 % of the samples were aware of sources of radiation pollution. Table- 3 shows that most of the samples (25 %) were aware of pollutants of soil pollution, 20 % of the samples were aware of pollutants of air pollution, water pollution, noise pollution, radiation pollution and thermal pollution. Table-4 reveals that 20 % of the samples were aware of ill health effects due to water pollution, noise pollution and thermal pollution 15 % of the samples were aware of ill health effects due to air pollution and 10 % of the samples were aware of ill health effects due to soil pollution and radiation pollution. Thus, proper strategies for environmental education and legislation should be enforced.